Social Anxiety-Impulsivity Subgroups and Links to Later Emotional Adjustment in Adolescence: A Latent Transition Analysis. (November 2020) - Van Zalk, Nejra; Tillfors, Maria; Mörtberg, Ewa
A growing body of research has acknowledged the heterogeneity of subclinical social anxiety, identifying a subgroup of individuals who exhibit high levels of impulsivity. In a sample of Swedish early adolescents ( N = 2, 509, M age = 13.64; 52.8% girls), we conducted latent transition analyses (LTA) to identify four classes of subclinical social anxiety-impulsivity across three time points. We identified a Low Social Anxiety-Low Impulsivity class, as well as a High Anxiety-High Impulsivity class for girls and boys, which had high levels of Time-4 internalizing problems. The latter class was less stable but larger for boys. There was also a more typical High Anxiety-Low Impulsivity class for both genders. Nevertheless, Low Anxiety-High Impulsivity girls and boys fared the worst in terms of both internalizing and externalizing problems later on. To our knowledge, this is the first study to adopt an LTA framework to investigate trajectories of early adolescent social anxiety-impulsivity over time.